Significance of galactinol and raffinose family oligosaccharide synthesis in plants - Sengupta, Sonali; Mukherjee, Sritama; Basak, Papri; Majumder, Arun L. (Frontiers in Plant Science, 2015)
Abiotic stress induces differential expression of genes responsible for the synthesis of Raffinose series of Oligosaccharides (RFOs) in plants. RFOs are described as the most widespread D-galactose containing oligosaccharides in higher plants. Biosynthesis of RFOs begin with the activity of Galactinol synthase (GolS; EC 2.4.1.123), a GT8 family glycosyltransferase that galactosylates myo-inositol to produce galactinol. Raffinose and the subsequent higher molecular weight RFOs (Stachyose, Verbascose and Ajugose) are synthesized from sucrose by the subsequent addition of activated galactose moieties donated by Galactinol. Interestingly, GolS, the key enzyme of this pathway is functional only in the flowering plants. It is thus assumed that RFO synthesis is a specialized metabolic event in higher plants; although it is not known whether lower plant groups synthesize any galactinol or RFOs. In higher plants, several functional importance of RFOs have been reported, e.g. RFOs protect the embryo from maturation associated desiccation, are predominant transport carbohydrate in some plant families, act as signaling molecule following pathogen attack and wounding and accumulate in vegetative tissues in response to a range of abiotic stresses. However, the loss-of-function mutants reported so far fail to show any perturbation in those biological functions. The role of RFOs in biotic and abiotic stress is therefore still in debateand their specificity and related components remains to be demonstrated. The present review discusses the biology and stress-linked regulation of this less studied extension of inositol metabolic pathway.